Pengembangan Edible Sensor Berbasis Ekstrak Bunga Telang dan Kayu Secang untuk Monitoring Kesegaran Fillet Ikan Tuna - Azarine, Nadia Fawwaz (Fakultas Farmasi, 2026)
Tuna fillet is a food product with high nutritional value. However, it has a relatively short shelf life, requiring freshness monitoring. Conventional methods such as sensory, chemical, and microbiological analyses have several limitations, including long analysis time, high cost, and variable results. This study aimed to develop an edible freshness sensor based on natural pH indicators from butterfly pea flower extract and sappan wood extract using bacterial cellulose (nata de coco) as a membrane and to evaluate its ability to monitor the quality deterioration of tuna fillet. The sensor was prepared through immobilization of butterfly pea extract (1%) and sappan wood extract (0.75%) with the addition of polyvinyl alcohol (PVA) at 1.5% for 12 hours. The resulting sensor exhibited a response time of 3 minutes, good reproducibility with RSD < 5%, and a shelf life of 15 days for butterfly pea sensor and 16 days for sappan wood sensor at room temperature, and up to 19 days for both sensors under chiller storage. The sensor was applied to tuna fillet, and color changes were analyzed using mean RGB values and compared with quality parameters, including organoleptic test, pH, Total Volatile Bases Nitrogen (TVB N), and Total Plate Count (TPC). The results showed that the edible sensor was able to monitor the quality deterioration of tuna fillet under both room and chiller storage. The color of the butterfly pea sensor changed from grayish blue to gray and dark gray, while the sappan wood sensor changed from reddish brown to red and brick red. These color changes were consistent with the decrease in organoleptic scores and the increase in pH, TVB-N, and TPC values during fish spoilage. Therefore, the developed edible sensor has the potential to serve as a practical, rapid, and environmentally friendly indicator for monitoring tuna fillet freshness.
Validasi dan Finalisasi Repositori File 25 Juni 2026_Kholif Basri
Keywords: edible sensor; tuna fillet freshness; natural pH indicator; color change